Quelle revitalisation de l’occitan, langue minorée, dans le cadre de l’enseignement public ? Le combat de la FELCO (Fédération des enseignants de langue et culture d’oc) - Marie-Jeanne Verny (Glottopol)
FELCO is a federation of academic associations of Occitan teachers, modelled on the professional associations for specific disciplines. Its task is to defend the teaching of Occitan and to provide a forum for collective reflection and action. This article looks briefly at its history before focusing on how it operates today: what forms of commitment? What partners are involved in its work and negotiations?